Degradation of contaminants of emerging concern by UV/H2O2 for water reuse: Kinetics, mechanisms, and cytotoxicity analysis. (1st May 2020) - Huang, Ying; Kong, Minghao; Coffin, Scott; Cochran, Kristin H.; Westerman, Danielle C.; Schlenk, Daniel; Richardson, Susan D.; Lei, Lecheng; Dionysiou, Dionysios D.
Abstract: Advanced oxidation using UV and hydrogen peroxide (UV/H2 O2 ) has been widely applied to degrade contaminants of emerging concern (CECs) in wastewater for water reuse. This study investigated the degradation kinetics of mixed CECs by UV/H2 O2 under variable H2 O2 doses, including bisphenol A, estrone, diclofenac, ibuprofen, and triclosan. Reverse osmosis (RO) treated water samples from Orange County Water District's Groundwater Replenishment System (GWRS) potable reuse project were collected on different dates and utilized as reaction matrices with spiked additions of chemicals (CECs and H2 O2 ) to assess the application of UV/H2 O2 . Possible degradation pathways of selected CECs were proposed based on high resolution mass spectrometry identification of transformation products (TPs). Toxicity assessments included cytotoxicity, aryl hydrocarbon receptor-binding activity, and estrogen receptor-binding activity, in order to evaluate potential environmental impacts resulting from CEC degradation by UV/H2 O2 . Cytotoxicity and estrogenic activity were significantly reduced during the degradation of mixed CECs in Milli-Q water by UV/H2 O2 with high UV fluence (3200 mJ cm −2 ). However, in GWRS RO-treated water samples collected in April 2017, the cytotoxicity and estrogen activity of spiked CEC-mixture after UV/H2 O2 treatment were not significantly eliminated; this might be due to the high concentration of target CEC and their TPs, which was possibly affected by the varied quality of the secondary treatment influent at this facility such as sewer-shed and wastewater discharges. This study aimed to provide insight on the impacts of post-UV/H2 O2 CECs and TPs on human and ecological health at cellular level. Graphical abstract: Image 1 Highlights: Present resulting toxicity during single CEC degradation by UV/H2 O2 . Show resulting toxicity of spiked CECs degraded by UV/H2 O2 in RO samples. Possible degradation pathways of selected CECs were proposed. Toxicity analysis at cellular level shows the risk of post-UV/H2 O2 on human and wildlife.